A study on the agency work industry in Singapore - Ang, Khim Wee (2010)
Agency work is a conundrum. It lowers search costs but undermines employment conditions and rights; it offers job flexibility but compromises on job security. While there has been substantial research on the agency work industry in the United States, Europe and Japan, little has been done in Asia, including Singapore.